Teknik Pembacaan Media Puzzle Huruf di Sekolah Dasar Kalimantan Tengah - Tedy Tedy; Ruth Stevani; Rusdiana Tamara; Yuliani Yuliani (Yayasan Literasi Sains Indonesia, 2023)
The author's research focused on students in an elementary school in Palangka Raya. The author found that there were students who were not familiar with alphabetic or numeric literacy, so students could not continue the reading process. In addition, based on the regular activities of students with various seriousness, it is time for teachers to provide opportunities, freedom and time for students to be creative, relieve fatigue through games, namely playing puzzles. This research is a qualitative research with data collection tools through the process of interviewing research subjects. Qualitative data is in the form of information regarding the implementation of learning using the game method with letter puzzle media carried out by teachers and students. The results of the study show the use or logical consequence of the puzzle media that the puzzle media is able to arouse student discipline based on awareness and exploration of the meaning of both obeying and breaking the rules in the student's discipline space itself. The cognitive domain, through the media of puzzles being important, not only makes students happy to play, but helps children to memorize and/or remember what happened to them through puzzle games.